Specification for nickel-alloy electrodes for flux cored arc welding (American Welding Society ; Reproduced by World Engineering Xchange (WEX) with the prermission of AWS under royalty agreement, 2007)
"The composition, soundness, and properties of weld metal from nine grades of flux cored electrodes are specified. Standard electrode sizes together with their package forms and package sizes are detailed. This specification makes use of both U.S. Customary Units and the International System of Units (SI). Since these are not equivalent, each system must be used independently of the other."